A Luminal Glycoprotein Drives Dose-Dependent Diameter Expansion of the Drosophila melanogaster Hindgut Tube. - Syed, Z.A.; Bouge, A.L.; Byri, S.; Chavoshi, T.M.; Tang, E.; Bouhin, H.; van Dijk-Hard, I.F.; Uv, A. (PLoS Genetics, 2012)
An important step in epithelial organ development is size maturation of the organ lumen to attain correct dimensions. Here we show that the regulated expression of Tenectin (Tnc) is critical to shape the Drosophila melanogaster hindgut tube. Tnc is a secreted protein that fills the embryonic hindgut lumen during tube diameter expansion. Inside the lumen, Tnc contributes to detectable O-Glycans and forms a dense striated matrix. Loss of tnc causes a narrow hindgut tube, while Tnc over-expression drives tube dilation in a dose-dependent manner. Cellular analyses show that luminal accumulation of Tnc causes an increase in inner and outer tube diameter, and cell flattening within the tube wall, similar to the effects of a hydrostatic pressure in other systems. When Tnc expression is induced only in cells at one side of the tube wall, Tnc fills the lumen and equally affects all cells at the lumen perimeter, arguing that Tnc acts non-cell-autonomously. Moreover, when Tnc expression is directed to a segment of a tube, its luminal accumulation is restricted to this segment and affects the surrounding cells to promote a corresponding local diameter expansion. These findings suggest that deposition of Tnc into the lumen might contribute to expansion of the lumen volume, and thereby to stretching of the tube wall. Consistent with such an idea, ectopic expression of Tnc in different developing epithelial tubes is sufficient to cause dilation, while epidermal Tnc expression has no effect on morphology. Together, the results show that epithelial tube diameter can be modelled by regulating the levels and pattern of expression of a single luminal glycoprotein.